Uterine transposition for gynecological cancers. Issue 3 (March 2021) - Baiocchi, Glauco; Vieira, Marcelo; Moretti-Marques, Renato; Mantoan, Henrique; Faloppa, Carlos; Damasceno, Rachel Cruz Fraga; Paula, Sálua Oliveira Calil; Tsunoda, Audrey Tieko; Ribeiro, Reitan
Abstract : Objective: Uterine transposition has emerged as an alternative for fertility preservation in women with pelvic malignancies that require radiotherapy. The goal of this study was to evaluate the short-term outcomes of patients undergoing uterine transposition after trachelectomy for cervical cancer or before chemoradiation for vaginal cancer. Methods: We retrospectively evaluated patients with early stage cervical cancer after radical trachelectomy or with vaginal cancer with indication for pelvic radiation who had uterine transposition performed as fertility sparing strategy. Results: Four patients with cervical cancer and one patient with vaginal cancer were included. Median age was 32 years (range 28–38). All patients had squamous cell carcinomas. All patients with cervical cancer had radical trachelectomies with sentinel lymph node dissection (SLN). Two of these patients also had pelvic lymphadenectomies. Indications for adjuvant radiotherapy was due to Sedlis criteria in two patients and to lymph node metastasis in the other two patients. The patient with stage IIB vaginal cancer was recommended primary chemoradiation. All patients underwent uterine transposition before radiotherapy. The median uterine transposition surgical time was 90 min (range 80-205) and no early complications (30 days) occurred. Average time from uterine transposition to start of radiotherapy was 16 days (10–28). After radiation, the uterus along with the ovaries and tubes were repositioned and the residual cervix sutured to the vagina. One patient declined uterine reimplantation after radiation and underwent a hysterectomy. After a median follow-up of 25 months (range 1–30), all patients were without evidence of disease. All patients with preserved uterus have normal menses after treatment. One patient has attempted to conceive with IVF techniques without success. Conclusions: Uterine transposition may be an option in selected patients with cervical and vaginal cancers who want to preserve fertility. However, further studies that address its oncological safety and obstetrical outcomes are encouraged.